RETRACTED ARTICLE: Long non-coding RNA CCAT2 acts as an oncogene in osteosarcoma through regulation of miR-200b/VEGF - Juntao Liu; Dehai Kong; Deping Sun; Jianmin Li (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal  Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Juntao Liu, Dehai Kong, Deping Sun & Jianmin Li (2019) Long non-coding RNA CCAT2 acts as an oncogene in osteosarcoma through regulation of miR-200b/VEGF. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 2994–3003, DOI: 10.1080/21691401.2019.1640229Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors checked their data and confirmed there are fundamental errors present. Therefore, they have agreed to the retraction of this article. The authors apologise for this oversight.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.